2009
DOI: 10.1080/09638280902803765
|View full text |Cite
|
Sign up to set email alerts
|

The practice of physical medicine and rehabilitation in sub-Saharan Africa and Antarctica: A white paper or a black mark?

Abstract: Antarctica is doing fine. Africa is in a crisis. Local medical schools, hospitals doctors, and persons with disability; along with foreign volunteers, aid groups and policymakers can impact the crisis. However government--specifically national ministries of health--is ultimately responsible for the health and well-being of citizens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 5 publications
1
15
0
1
Order By: Relevance
“…Consistent with previous studies (Tinney et al, 2007;Haig et al, 2009), no physiatrist was identified in the current study. The absence of rehabilitation physicians in Ghana and most of sub-Sahara represents a core barrier to providing the comprehensive rehabilitation care consistent with established international standards.…”
Section: Human Resourcessupporting
confidence: 82%
See 3 more Smart Citations
“…Consistent with previous studies (Tinney et al, 2007;Haig et al, 2009), no physiatrist was identified in the current study. The absence of rehabilitation physicians in Ghana and most of sub-Sahara represents a core barrier to providing the comprehensive rehabilitation care consistent with established international standards.…”
Section: Human Resourcessupporting
confidence: 82%
“…The absence of rehabilitation physicians in Ghana and most of sub-Sahara represents a core barrier to providing the comprehensive rehabilitation care consistent with established international standards. In the absence of physiatry, rehabilitation is often provided primarily through PT, occurring primarily in outpatient physiotherapy centres that may or may not be associated with a hospital (Tinney et al, 2007;Haig et al, 2009;Christian et al, 2011). The primary burden of rehabilitation care falls on the PT who is expected to have extensive medical knowledge and appropriate clinical decisionmaking ability, but often in the absence of adequate resources (Dunleavy, 2007).…”
Section: Human Resourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…22 However, there are dissenters to this position. Haig et al 43 in their 2009 article describe CBR as a politically expedient way to allocate the least amount of money possible to the problem. They suggest that CBR is a process of delegating highly skilled rehabilitation treatment to cheap uneducated locals without proper training or sufficient input from medical professionals.…”
Section: Types Of Service Provisionmentioning
confidence: 99%